Previous pelvic surgery and ectopic pregnancy in the epidemiology of ectopic pregnancy - Zapata, Betsy (2015)
Objectives: To determine incidence, epidemiological and clinical characteristics, and surgical management of patients with diagnosis of ectopic pregnancy. Design: Descriptive and retrospective study. Institution: Hospital Nacional Docente Materno Infantil (HONADOMANI) San Bartolomé. Participants: Women with ectopic pregnancy. Methods: Review of medical records of 46 patients with ectopic pregnancy diagnosis in the period May 2013 – April 2014. Main outcome measures: Ectopic pregnancy clinical findings. Results: Incidence of ectopic pregnancy in the 46 patients studied was 0.63% or 1/157 births. Patients were mostly multiparous, 89% 20-40 years old, 37% with 5-7 weeks amenorrhea, 20% with history of ectopic pregnancy, 39% had previous pelvic surgery, 59% presented typical symptomatology (amenorrhea, abdominal pain and vaginal bleeding). Transvaginal ultrasound was performed in all patients and sonographic findings were presence of adnexal mass and free fluid in the posterior fornix; 54% of ectopic pregnancies were complicated; 89% had tubal location. Laparotomy was performed in 48% and pathology confirmation was obtained in other 48%. Conclusions: In the population studied ectopic pregnancy continued being a gynecological and obstetrical emergency, half of them complicated. It should be suspected in cases of previous pelvic surgery and previous ectopic pregnancy. Transvaginal ultrasound was the main diagnostic tool, and surgery the elective procedure.